2014
DOI: 10.1007/s10452-014-9486-z
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of embryos and hatchlings of the invasive apple snail Pomacea maculata to estuarine conditions

Abstract: One of the most successful groups of invasive consumers worldwide is freshwater snails of the family Ampullariidae, including Pomacea maculata, yet little is known about snail survival and growth in the range of conditions found in estuarine ecosystems. Here, we provide an experimental assessment of P. maculata survivability in estuarine conditions, documenting: (1) egg susceptibility to tidal inundation (2) salinity tolerance of snails, and (3) salinity effects on hatchling growth. Results indicate that estua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Abiotic conditions that are beyond tolerances of an organism may caus immediate death or inhibit its ability to establish new populations and become invasive [21]. Some studies showed that the growth and reproduction of P. canaliculata are driven by water temperature [30,31], pH [9,20], dissolved oxygen [27], and salinity [28,29]. Our results indicated that genetic variation of P. canaliculata was significantly correlated with the concentration of dissolved oxygen and pH (p < 0.05).…”
Section: Correlation Between Genetic and Water Quality Parametersmentioning
confidence: 65%
See 1 more Smart Citation
“…Abiotic conditions that are beyond tolerances of an organism may caus immediate death or inhibit its ability to establish new populations and become invasive [21]. Some studies showed that the growth and reproduction of P. canaliculata are driven by water temperature [30,31], pH [9,20], dissolved oxygen [27], and salinity [28,29]. Our results indicated that genetic variation of P. canaliculata was significantly correlated with the concentration of dissolved oxygen and pH (p < 0.05).…”
Section: Correlation Between Genetic and Water Quality Parametersmentioning
confidence: 65%
“…Abiotic conditions of a system may prevent establishment or allow it to thrive, reproduce, and become invasive. For freshwater snails, key abiotic water quality variables are likely to be the concentration of calcium carbonate [25,26], pH [9,20], concentration of dissolved oxygen [27], salinity [28,29], and temperature [30,31]. Previous studies on the invasion of P. canaliculata mainly focused on distribution [19], associated diseases [32,33], phylogeny [15,19,22], and taxonomy [34].…”
Section: Introductionmentioning
confidence: 99%
“…1) possible genetic exchange, genetic bottlenecks and genetic drift (Matsukura et al 2013;Shirk et al 2014), which could be the result of the initial founder event that led to speciation in P. canaliculata and P. maculata (Freeland et al 2011); 2) the introduction of alien species to a non-native location may not be directly from the native range, but from a successful invasive population elsewhere, which could be the result of the bridge-head effect (Eric et al 2010); 3) sample numbers of Pomacea for each country were significantly different for this study, so further genetic analysis is needed to clarify this (Hayes et al 2008); 4) growth and reproduction of P. canaliculata and P. maculata are closely related to water temperature: many studies showed that the snail was not adapted to low temperatures (Andree and López 2013;Byers et al 2013;Hayes et al 2015;Bernatis et al 2016). In addition, climate change (Byers et al 2013) and environment factors such as pH (Byers et al 2013), calcium carbonate (White et al 2007;Perlman 2016), dissolved oxygen (Seuffert and Martín 2009), salinity (Verbrugge et al 2012;Martin and Valentine 2014) may affect their life history. Pomacea was introduced to many countries as food, but its economic potential was overestimated.…”
Section: Countrymentioning
confidence: 94%
“…Few studies have examined the effects of salinity on apple snails; however, adult P. canaliculata and P. maculata are capable of tolerating salinities ranging from 3‰–8‰ (Ramakrishnan, ; Bernatis et al ., ). Apple snails will not survive in estuarine and salt‐water conditions, although the eggs of P. maculata can survive short term exposure to salinities above 10‰ (Martin & Valentine, ). Hatchlings, and to a lesser extent juveniles, of both species are less tolerant of saline conditions than eggs and adults and suffer high mortality at salinities above 8‰.…”
Section: Effects Of Water Quality On Apple Snailsmentioning
confidence: 99%